PENGEMBANGAN STRATEGI PENINGKATAN DAYA SAING PRODUK BATIK DENGAN MENGGUNAKAN ANALISIS VALUE CHAIN - Suhartini Suhartini (Matrik : Jurnal Manajemen dan Teknik Industri Produksi, 2018)
Batik industry development is very rapid. This will increase the economic value added and employment.and expected to increase in country's foreign exchange. This purpose can be success with approach strategy is value chain analysis and implemented, SWOT, Competitiveness Diamond and Critical Success Factor. Value Chain Analysis can be used as a strategic analysis tool for better understanding of the competitive advantage, which the company can increase the value added (value added) and a decrease in cost to make the business more competitive. The result of this study is recommendations of strategic. The recommendation can be increase of batik industry productivity.